Multiple metastatic tuberculosis abscesses in a patient with Pott disease and lung tuberculosis - Saral, Y; Coskun, BK; Ozturk, P; Bulut, Y; Çobanoglu, B (Blackwell Publishing, 2005)
The incidence of tuberculosis in Western countries is rising, and continued vigilance together with an awareness of its protean manifestations is essential. Cutaneous tuberculosis is a relatively rare manifestation of the disease, accounting for only 1% of extrapulmonary cases of tuberculosis and 0.14% of all reported cases of tuberculosis. A 19-year-old male patient was admitted to our clinic with skin lesions both at the front and at the back of his body. With clinical findings, histopathology, polymerase chain reaction, PA lung graph, and computerised tomography, the patient was diagnosed with metastatic tuberculosis abscess associated with lung tuberculosis and Pott's disease. Antituberculosis drugs were administered. An increased awareness of the re-emergence of cutaneous tuberculosis will allow for the proper diagnosis and management of this increasing common skin disorder.
Keywords: Cutaneous Tuberculosis; Children; Gumma; Skin